Collective Rights of Persons Engaged in Gainful Employment Outside the Employment Relationship – en Outline of the Issue - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The main objective of the following study is to introduce readers to the issue of the 2nd National Scientific Conference in the series “Atypical Employment Relations” organized on 3 October 2019 by the Centre for Atypical Employment Relations of the University of Lodz. The consequence of extending the right of coalition to persons performing paid work outside the employment relationship was that they were guaranteed important collective rights, which until 1 January 2019 were reserved primarily for employees. The rights which Polish legislator ensured to non-employees include the right to equal treatment in employment due to membership in a trade union or performing trade union functions; the right to bargain with a view to the conclusion of collective agreement and other collective agreements; the right to bargain to resolve collective disputes and the right to organize strikes and other forms of protest, as well as the right to protect union activists. The author positively assesses the extension of collective rights to people engaged in gainful employment outside the employment relationship, noting a number of flaws and shortcomings of the analyzed norms. The manner of regulating this matter, through the mechanism of referring to the relevant provisions regulating the situation of employees, the statutory equalization of the scope of collective rights of non-employees with the situation of employees, the lack of criteria differentiating these rights, as well as the adopted model of trade union representation based on company trade unions, not taking into account the specific situation of people working for profit outside the employment relationship, are the reasons why the amendment to the trade union law is seen critically and requires further changes.